The Relationship between Motivation for Learning English as a Foreign Language and Perception of the Study of Theology in English Held by Years 1-4 Seminarians at St. Joseph’s Major Seminary Yangon, Myanmar - Zaw Htun Lin, Zaw Htun Lin; Orlando Rafael González González (Scholar: Human Sciences, 2021)
This quantitative study was intended to determine the relationship between motivation for learning English as a foreign language (EFL) and perception of the study of Theology in English at St. Joseph’s Major Seminary in Yangon, Myanmar. A total population of 100 seminarians from Years 1, 2, 3 and 4, enrolled in the academic year 2019-2020, participated in this study. The research instruments used for data collection were the Questionnaire of Motivation for Learning English as a Foreign Language Questionnaire (MLEFLQ) and the Perception of the Study of Theology in English Questionnaire (PSTEQ). Descriptive statistics (means and standard deviations) and correlational analysis (using Pearson’s correlation coefficient and multiple correlation coefficient) were performed on the collected data. The findings indicated that Years 1-4 seminarians, on average, had a high level of motivation for learning EFL, as well as a positive perception of the study of Theology in English. In relation to the three subscales comprising motivation for learning EFL (i.e., motivational intensity for learning EFL, desire to learn EFL, and attitude toward learning EFL), it was found the following: (a) the motivational intensity for learning EFL of Years 1-3 seminarians was high, whereas it was partially high for Year 4 seminarians; (b) the desire to learn EFL of Years 1-4 seminarians was high; and (c) the attitude toward learning EFL of Years 1-4 seminarians was positive. The results from the correlational analysis revealed the following: (a) for Year 1 seminarians, there was no significant relationship of motivation for learning EFL (in terms of its three comprising subscales) with perception of the study of Theology in English; (b) for Year 2 seminarians, there was a significant, strong multiple linear relationship of motivation for learning EFL (in terms of its three comprising subscales) with perception of the study of Theology in English; (c) for Year 3 seminarians, there was a significant, moderately strong multiple linear relationship of motivation for learning EFL (in terms of its three comprising subscales) with perception of the study of Theology in English; and (d) for Year 4 seminarians, there was a significant, weak linear relationship of desire to learn EFL with perception of the study of Theology in English. Based on the discussion of the findings, recommendations for action and further study are provided.